Application framework support for process-oriented software development. (1st January 2013) - Tegegne, Abel; Peyton, Liam
As organisations move their business processes online, it is becoming important for software development to be process-oriented. In particular, managed process applications are a class of business software that helps to improve operational efficiency in organisations by monitoring processes and reporting on performance. General purpose application development tools and model-driven architecture do not support run-time configurability of a managed process nor do they provide specific systematic support for integrated data collection, monitoring and reporting within a managed process. To facilitate such configurability and integrated data management, a model-based application framework is needed to address process-oriented software development. In this paper, we describe a prototype of such a framework, illustrating and evaluating the benefits, with a case study of a system developed for and used by a palliative care support team in Ottawa, Canada. In the case study, we illustrate how a managed process can be modelled using the prototype framework (including its' workflow, roles, entities, events, alerts and performance indicators).